STRUCTURAL AND PHYSICAL PROPERTIES OF REFRACTORY CORDIERITE PRECURSORS PREPARED FROM RICE HUSK SILICA WITH DIFFERENT MgO ADDITION - Simon Sembiring; Wasinton Simanjuntak; Situmeang Rudi; Riyanto Agus; Junaidi (Ceramics-Silikáty, 2018)

(untitled)
This study describes the structural and physical properties of refractory cordierite prepared from rice husk silica, which is sintered at a temperature of 1230 °C and followed by the addition of periclace (MgO) from 5 to 30% by weight. The phases formed and structure changes as a result of periclace addition were investigated using different characterization technique of x-ray diffraction (XRD) coupled with Rietveld analysis, and scanning electron microscopy (SEM). Density, porosity, hardness, bending strength and coefficient of thermal expansion are also measured. The results obtained revealed that the addition of periclace of 10 to 30% promoted the transformation of the cordierite to the forsterite and spinel, and the cordierite is practically undetectable. Addition of periclace was found to increase forsterite and decrease spinel. The presence of forsterite and spinel resulted in increased of density, hardness, bending strength, and thermal expansion coefficient, as well as decreased porosity. The coefficient of thermal expansion of the samples with the addition of 10-30% periclace reach the relatively constant value of 8.2 × 10-6 /°C, with the main crystalline phase is forsterite, followed by spinel in smaller quantities.